Academic Stress in Students of the Faculty of Health Sciences and the Human Being of the State University of Bolívar - Paredes Garcés, Wilson (2021)
Studying and describing the level of stress in different facets of student life is the purpose and unit of analysis of this work, which through a qualitative-quantitative approach reaches a descriptive level for 187 Nursing students from the State University of Bolívar who are the sample stratified from a universe of 364 people with a 5% admissible error. It allowed us to reject the Ho: "Health students are NOT stressed in academic settings." evaluated with the SISCO test evaluated concern or nervousness, academic conditions (presence of exams, essays, research works that imply a time limit), applied for a week by the researchers. High levels of stress were observed in the responses: sometimes, usually and always classified as "frequent" during the presence of the stressor. "In Ecuador, psychological stress was positively correlated with indicators of health, loneliness, psychological inflexibility, alcohol consumption, anxiety, depression, the highest level of stress was significantly higher in women than in men" (Ruisoto, 'López, Paladinez, & all ., 2020). The conclusions are that the academic environment causes stress especially in health students due to stressful characteristics in tests, exams, time limitations and the attitude of teachers with little empathy and traditional methods.